Operettesangerinden i ordsøen: Om Arthur Schnitzlers Fräulein Else - Bach, Hardy (K&K - Kultur og Klasse, 2008)
The Operetta Singer in the Sea of Words: About Arthur Schnitzler’s Fräulein Else: Arthur Schnitzler’s famous short story »Fräulein Else« (1924) is usually read as a social-psychological study. A consensus about how to perceive the protagonist has never been obtained, although the interior monologue technique should give the reader the best possibilities to understand the heroine. Is Else a doughty girl who fights the oppression of women or is she an unhappy victim because of the environment abusing her? Does she commit suicide or is she rather just pretending? The essay is an attempt to go behind these questions by demonstrating the possibility that Schnitzler quite deliberate blurs these elements of the story. The essay asserts that Schnitzler, rather than giving a social-psychological study, is trying to let the story tell about itself. Fräulein Else thus becomes a metapoetical text which reflects not only on itself but also on the ‘everlasting conditions’ of literature and of writer. The stream of consciousness is thus possibly soul scrutiny but first and foremost an attempt to put the impossible into practice: to let the text tell about itself so to say ‘from within’.